Nontraditional Approach to Studying Science and Technology - Hockicko, Peter (Communications - Scientific letters of the University of Zilina, 2010)
The present paper informs about nontraditional teaching activities which can help teachers and students to reach better results in the studying process. Information and communication technologies (ICT) in physics education can help to increase the effectivity of the teaching process. For students, physical analysis using computer programs is more demonstrative, learning physical equations is quicker, understanding of the physical laws is easier. It is necessary to catch them young. Because of this reason the Children’s University of Zilina (CUZ) has been realized in the summer time for children attending elementary school. The questionnaires for children show that it is highly necessary to increase the number of presented experiments, to use multimedia in a larger extent, to develop their imagination and creativity, sense for team work. The interest in nature and technology subjects can be increased by developing the student’s imagination and thinking.